Assessing white matter ischemic damage in dementia patients by measurement of myelin proteins. - Barker, R; Wellington, D; Esiri, M; Love, S (2013)
White matter ischemia is difficult to quantify histologically. Myelin-associated glycoprotein (MAG) is highly susceptible to ischemia, being expressed only adaxonally, far from the oligodendrocyte cell body. Myelin-basic protein (MBP) and proteolipid protein (PLP) are expressed throughout the myelin sheath. We compared MAG, MBP, and PLP levels in parietal white matter homogenates from 17 vascular dementia (VaD), 49 Alzheimer's disease (AD), and 33 control brains, after assessing the post-mortem stability of these proteins. Small vessel disease (SVD) and cerebral amyloid angiopathy (CAA) severity had been assessed in paraffin sections. The concentration of MAG remained stable post-mortem, declined with increasing SVD, and was significantly lower in VaD than controls. The concentration of MBP fell progressively post-mortem, limiting its diagnostic utility in this context. Proteolipid protein was stable post-mortem and increased significantly with SVD severity. The MAG/PLP ratio declined significantly with SVD and CAA severity. The MAG and PLP levels and MAG/PLP did not differ significantly between AD and control brains. We validated the utility of MAG and MAG/PLP measurements on analysis of 74 frontal white matter samples from an Oxford cohort in which SVD had previously been scored. MAG concentration and the MAG/PLP ratio are useful post-mortem measures of ante-mortem white matter ischemia.